AYDINLANMA FELSEFESİ VE SİYASAL MUHAFAZAKARLIK - Mehmet Vural (Felsefe Dünyası)
This study aims at giving an explanatory understanding of conservativism in regard to the philosophy of politics, and at discussing its place and future within our historical period. This study asserts that conservative philosophy of politics came about as a reaction against continental enlightenment, and became a political stance within French Revolution. This artical mainly considers the formation of conservative theory, and the relation between conservativism and the philosophy of enlightenment. Moreover, reactions to the philosophy of enlightenment arisen by religious, romantic and conservative thinkers have also been mentioned. Within the history of western thought, political conservativism emphasizes a serious tradition of thought, assumed to bear a rich philosophical heredity. Moreover, among modern philosophies of politics, it also stresses a highly comprehensive doctrine, and a philosophy of politics which has completely marked our historical period.